2015
DOI: 10.5380/revsbau.v9i3.63226
|View full text |Cite
|
Sign up to set email alerts
|

Análise Qualiquantitativa De Indivíduos Arbóreos Das Praças Centrais Do Município De Leme, Sp

Abstract: Planejar a arborização é indispensável para o desenvolvimento urbano e fundamental na salubridade ambiental, por ter influência direta sobre o bem-estar do homem em razão dos múltiplos benefícios proporcionados. O presente trabalho teve por objetivo identificar as espécies arbóreas de três praças da região central do município de Leme, SP. O método de inventário utilizado foi o Censo. A avaliação dos indivíduos arbóreos constou da determinação da espécie com suas variáveis dendrométricas, tais como: classe de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…The proportions of exotic and indigenous species and individuals in the squares of Curitiba are part of the reality presented in similar studies, which found between 51.61% and 58.82% of indigenous species, and between 40.20% and 67.45% of individuals of indigenous species (KRAMER;KRUPEK, 2012;TISCHER et al, 2014;LIMA et al, 2015;COSTA et al, 2017;SILVA et al, 2018).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The proportions of exotic and indigenous species and individuals in the squares of Curitiba are part of the reality presented in similar studies, which found between 51.61% and 58.82% of indigenous species, and between 40.20% and 67.45% of individuals of indigenous species (KRAMER;KRUPEK, 2012;TISCHER et al, 2014;LIMA et al, 2015;COSTA et al, 2017;SILVA et al, 2018).…”
Section: Discussionsupporting
confidence: 55%
“…When compared to similar studies in other Brazilian cities, the values found for species and individuals per square and hectare of the contemporary style and in Curitiba as general are noted to be low. In São Gabriel-RS, there are 37.00 ±6.56 species per square, 28.65 ±4.38 species per hectare, 181.00 ±69.40 individuals per square, and 143.34 ±66.74 individuals per hectare (OLIVEIRA-NEVES et al, 2016); in Guarapuava-PR, there are 30.80 ±13.55 species per square, 163.30 ±96.70 individuals per square, and 102.33 ±54.95 individuals per hectare (KRAMER; KRUPEK, 2012); in Leme-SP, there are 25.00 ±16.09 species per square, and 98.67 ±72.13 individuals per square (TISCHER et al, 2014); and in Nova Xavantina-MT, there are 15.17 ±10.95 species per square and 68.91 ±39.86 individuals per square (LIMA et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The arboreal composition of squares' landscape has been described in several Brazilian regions (Batista et al, 2013;Tischer et al, 2014;Gomes et al, 2016). José Bonifácio Square shows a large diversity of trees implemented on the historic square.…”
Section: The Arboreal Composition and Ecological Importance Of José Bonifácio Squarementioning
confidence: 99%
“…One of José Bonifácio Square's significant results is related to the high frequency of individuals and species of Bignoniaceae, Arecaceae, and Fabaceae. A few studies highlighted Bignoniaceae and Arecaceae for their noteworthy richness of species in several Brazilian squares (Romani et al, 2012;Tischer et al, 2014;Gomes et al, 2016). Fabaceae has already been recognized for its high frequency in urban greening across Brazil.…”
Section: The Arboreal Composition and Ecological Importance Of José Bonifácio Squarementioning
confidence: 99%
“…As áreas verdes são componentes relevantes para o da população urbana, nestas áreas as árvores são de suma importância tanto por questões ambientais, estéticas como para o bem-estar humano Silva et al (2017). Conforme Tischer et al (2014) as praças e jardins ajudam na retenção e ciclagem da água, agem como quebra ventos, além de oferecer condições de sobrevivência para fauna da região.…”
Section: Introductionunclassified